Do Structural Policies Affect Macroeconomic Stability? - Ziemann, Volker (OECD Economics Department Working Papers, 2013)
Using a panel of OECD countries, this study assesses the linkages between structural policies and macroeconomic stability. Business cycle and time-series characteristics of GDP and its components are employed to define various measures for economic instability and for the persistence of adverse shocks. The results suggest that some growth-enhancing policies such as lowering employment protection also reduce macroeconomic fluctuations, while others may generate trade-offs between growth and stability. A pro-cyclical tax structure seems to help alleviating the persistence of adverse macroeconomic shocks